Profit Management In The View Of Islamic Business Ethics - M. Noor Bustomi; Indah Maslaha; Achmad Basofitrah; Imelda Musarofah; M. Jamaluddin Affan (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
This study aims to critically investigate the practice of profit management through the lens of Islamic business ethics within the Indonesian corporate context. While profit management is often viewed as a technical accounting maneuver, this research deconstructs its moral implications by integrating prophetic values—shiddiq (honesty), amanah (responsibility), tabligh (transparency), and fathanah (intelligence)—as a framework for financial integrity. A qualitative descriptive approach was employed, utilizing a systematic library research method. The study synthesized 10 primary and secondary sources, including Quranic texts, Hadith, and contemporary academic journals indexed in major databases. Content analysis was applied to reconcile the tension between conventional agency theory and the Maqasid al-Shari’ah framework, focusing on how spiritual internalisation moderates opportunistic managerial behaviour. The results reveal a significant paradigm shift; profit management is categorized into two domains: 'permissible' when aimed at organizational stability (maslahah) without deceit, and 'prohibited' (haram) when it involves tadlis (manipulation) or khiyanah (breach of trust). The study finds that in Indonesia, the